Policy-based Resource Allocation in Hierarchical Virtual Organizations for Global Grids - Kim, Kyong Hoon; Buyya, Rajkumar (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2006)
In previous years, many studies have been conducted on grid computing, in which users and resource providers organize various virtual organizations (VOs) to share resources and services. A VO organizes other sub-VOs for the purpose of achieving the VO goal, which forms the hierarchical VO environment. In this paper, we model and formalize the resource allocation problem in hierarchical VOs. Resource providers and VOs agree upon the VO resource sharing policy, such as resource sharing amount and resource usage cost for VOs. We provide the resource allocation scheme of a VO resource broker to minimize the total cost in order to meet a user's job deadline. In addition, we deal with several cost adjustment methods in resource providers to utilize their resources efficiently in hierarchical VOs